Theological deviations and their impact on the Arab Spring: An analytical and critical study on Yemen and Syria / Ebrahim Mohammed Abdo Mousi - Ebrahim Mohammed , Abdo Mousi (2018)
While the nation is undergoing a sever crisis in its political and social course, Arabic revolutions, which have been known as Arab Spring, have worsened this crisis. It was expected that Arab people would find an outlet to the despicable tyranny from which they had suffered for decades. However, it is found that that Arab Spring has got the door opened to some intellectually deviant trends, resulting in changing its course and shattering the hopes of peoples. Therefore, this study is needed to highlight the effect of these deviations on the Arab Spring Phenomenon and on turning its equation. One of the study’s objectives was to identify some of the doctrinally deviants trends that belong to the Sunni, which are the organizations of ISIS, and Houthi. The study aimed at showing the state of the Arab Spring and the effect of such doctrines on it and on the Islamic World as well as highlighting the issues of the ruler’s disobedience and the legitimacy of change. This study made use of the Yemeni and Syrian revolutions as models of the Arab Spring revolutions. The study adopted the inductive, critical and analytical approach. The findings showed several results one of which is identifying the reasons behind doctrinal deviation and the reasons for the Arab Spring. The study proposed that neutrality should be foregrounded in judging these trends and Arab revolutions, so they should not be judged on the basis of one view rather than the other, as some of the scholars’ sayings are taken into considerations while other evidences and sayings of other scholars are not. The study also revealed the most influential and dangerous groups on the Arab Spring, which were recognized as those groups that have recently followed Shia, Kharijite, and Murjia, revealing the profound impact that these groups had on changing the Arab Spring course. The study pointed out the contrast between Takfiri ideology and reconciling ideology and the phenomenon of excessiveness and terrorism, which has been sometimes overstated and sometimes understated. It was found out that the conflict among civilizations has to be taken for granted, which cannot be achieved unless we emphasize the law of contest.